Identifikasi Kesulitan Belajar Siswa pada Pelajaran Kimia Kelas XI MIPA di MAN 2 Mataram - Lestari, Citra; Aliefman Hakim; Lalu Rudyat Telly Savalas (FKIP University of Mataram, 2024)
This research aims to identify students' learning difficulties in class XI MIPA chemistry learning at MAN 2 Mataram. This study is descriptive research with a qualitative approach. The population of this research was 285 students and distributed to 8 classes. The total sample of 74 students was obtained using simple random sampling method. The data were collected using questionnaires and interviews. The data were analyzed by applying a percentage formula, complemented by an in-depth explanation of the responses provided by the interviewed respondents. The research results showed that students' learning difficulties were into the high category. Students experience difficulties with internal factors (74%), which include physical and mental conditions (80%) as well as motivation and interests (67.5%). Furthermore, learning implementation factors (74%) include teacher explanations (76.5%), student participation (74%), and assignments (71.4%). Lastly, external factors (75%) include economic difficulties (86.4%), support from the environment and family (71%), and support from the school (78.6%). Hence, the aforementioned factors contributed to the learning difficulty among class XI MIPA students at MAN 2 Mataram.